Long-term preservation of yeast cultures in liquid nitrogen - Hubálek, Z; Kocková-Kratochvílová, A (Folia microbiologica, 1982)
Nineteen strains of taxonomically diverse yeast species tested survived freezing and subsequent five-year storage in liquid nitrogen at - 196 degrees C, using a medium M 2 composed of malt extract, yeast extract, peptone, calf serum and dimethyl sulfoxide. Viability of the yeast cultures after long-term storage ranged from 5 to 97% (average 62%) compared with the viability of the cultures prior to freezing. The use of liquid nitrogen refrigeration for preserving yeast cultures is strongly advocated.
Keywords: kvasinky; Yeasts; Refrigeration; Nitrogen; dusík; chlazení